KEBIJAKAN HUKUM BISNIS TERHADAP JAMINAN DAN TANTANGAN DIGITALISASI DALAM TRANSAKSI BISNIS SECARA ONLINE DI ERA DIGITAL - Bancin, Jusuf Sugiarto; Jhon Cristmas Damanik; Ronael Jon Feriando Sihotang; Toman Sony Tambunan (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
The problem in this study is how the business law policy regulates guarantees in online transactions and how effective its implementation is in providing legal certainty for business actors. This study aims to analyze business law regulations that regulate guarantees in online transactions and examine the obstacles and solutions to their implementation in the digital era. The research method used is the normative legal method with a qualitative approach. Data collection techniques are carried out through literature studies, documentation of regulations, and analysis of relevant cases. Data analysis techniques are carried out descriptively analytically against applicable legal norms. The results of the study indicate that business law policies in Indonesia are not yet fully adaptive to the dynamics of online transactions, especially in terms of proof of guarantees, validity of digital documents, and settlement mechanisms.